2000
DOI: 10.1128/jvi.74.14.6316-6323.2000
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence of Hemagglutinin Glycosylation and Neuraminidase as Regulators of Influenza Virus Growth: a Study by Reverse Genetics

Abstract: The hemagglutinin (HA) of fowl plague virus A/FPV/Rostock/34 (H7N1) carries two N-linked oligosaccharides attached to Asn123 and Asn149 in close vicinity to the receptor-binding pocket. In previous studies in which HA mutants lacking either one (mutants G1 and G2) or both (mutant G1,2) glycosylation sites had been expressed from a simian virus 40 vector, we showed that these glycans regulate receptor binding affinity (M. Ohuchi, R. Ohuchi, A. Feldmann, and H. D. Klenk, J. Virol. 71:8377-8384, 1997). We have no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
192
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(206 citation statements)
references
References 41 publications
10
192
0
4
Order By: Relevance
“…After incubation for 1 h, the cells were washed three times with PBS and then overlaid with DMEM containing 0.8 % agar (Sigma) and 2 % FBS. The infected cells were incubated for an additional 72 h, and the plaques were visualized by staining with 0.1 % crystal violet in a 10 % formaldehyde solution (Wagner et al, 2000). For each virus, 10 well-spaced plaques were measured using the GNU image manipulation program (version 2.8; www.gimp.org), as described previously (Negovetich & Webster, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After incubation for 1 h, the cells were washed three times with PBS and then overlaid with DMEM containing 0.8 % agar (Sigma) and 2 % FBS. The infected cells were incubated for an additional 72 h, and the plaques were visualized by staining with 0.1 % crystal violet in a 10 % formaldehyde solution (Wagner et al, 2000). For each virus, 10 well-spaced plaques were measured using the GNU image manipulation program (version 2.8; www.gimp.org), as described previously (Negovetich & Webster, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…of 0.001 in DMEM for 1 h. The unbound viruses were washed with PBS, and serum-free DMEM was added. The cells were incubated at 37 uC under 5 % CO 2 , and the virus titres in the supernatant were monitored periodically by the determination of the TCID 50 on CEF cells (Wagner et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…NA stalk deletions have been shown to reduce the enzymatic activity of the protein [14] and, presumably, adversely affect the spread of the virus to uninfected cells. Secondly, changes in the HA gene that compensate for a shortened N stalk have been described, including increased glycosylation near the receptor binding site thereby decreasing receptor binding affinity [15,16]. Sub-lineage I displayed this hyperglycosylation, with five predicted N-glycosylations sites in the HA gene compared to only three in sub-lineage II, which did not contain the Nstalk deletion.…”
Section: Fig 2 Unrooted Phylogenetic Tree Of the H6 Ha Nucleotide Sementioning
confidence: 99%
“…Modulation of HA and NA activities has been shown to be important for viral growth (Mitnaul et al, 2000;Wagner et al, 2000) and protein yield (Adamo et al, 2009;Jing et al, 2012). We previously showed that viruses with WT or chimeric A/VN/1203 NA (JV20 and JV24, respectively) had similar NA activity (Adamo et al, 2009).…”
mentioning
confidence: 99%